War and stature: Growing up during the Nigerian civil war - Richard Akresh; Sonia R. Bhalotra; Marinella Leone; Una O. Osili (Institute for the Study of Labor (IZA), 2011)
The Nigerian civil war of 1967-70 was precipitated by secession of the Igbo-dominated south-eastern region to create the state of Biafra. It was the first civil war in Africa, the predecessor of many. We investigate the legacies of this war four decades later. Using variation across ethnicity and cohort, we identify significant long run impacts on human health capital. Individuals exposed to the war at all ages between birth and adolescence exhibit reduced adult stature and these impacts are largest in adolescence. Adult stature is portentous of reduced life expectancy and lower earnings.
urn:nbn:de:101:1-201201104519
Keywords: I12; O12; J13; 330; war; height; early life; human capital investments; Nigeria; Bürgerkrieg; Unabhängigkeitsbewegung; Ethnische Gruppe; Soziale Lage; Persönlichkeitspsychologie; Gesundheit; Biologische Daten; Einkommen; Nigeria